Preparation and Structure Classification of Heteraspiro[m.n]alkanes - Undheim, Kjell (Synthesis, 2014)
The fundamental spirane framework consists of two monocyclic rings linked in an orthogonal relationship by a common ring atom. In spiranes with no annular heteroatom, four carbon atoms are bonded directly to the quaternary spirocarbon. The spirocarbon may be the site of a stereogenic centre and stereoisomerism. This review covers families of spiranes where one or both rings carry additional annular heteroatoms, mainly N, O or S. The heteroatoms are indicated by replacement prefixes. In general, the term ‘hetera’ denotes a nonspecified annulated heteroatom which may be N, O, or S. The presentation is arranged with preference for the size of the monocyclic rings and thereafter the nature of the annular heteroatoms.In general, rigid spirocyclic structures provide wide variations of spatial disposition of the functional groups. When the spirane skeleton consists of small- or medium-sized rings, a rigid structure results that also confers stiffness onto molecules in which the spirane may be embedded. The rigidity of such systems provides a stiff framework for the attachment of pharmacophoric groups, or a rigid framework for metal coordination. Reference is made to a limited number of studies of physico-chemical properties of small-ring systems. Nitrogen-containing systems are most common.1 Introduction and Definitions2 Heteraspiro[2.m]alkanes3 Heteraspiro[3.m]alkanes4 Heteraspiro[4.m]alkanes5 Heteraspiro[5.m]alkanes
Keywords: spirofused-ring systems; spiro nomenclature; stereoselective synthesis; cyclization; heterocycles; bioactive spiranes